2009
DOI: 10.1159/000236354
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Fetal Duodenum: A Postmortem Study

Abstract: Objective: To gather detailed morphometric data to be able to assess fetal development of the duodenum and its morphology. Material and Method: The present study was carried out on 222 human fetuses (114 males, 108 females) aged 9–40 weeks of gestation with no external pathology or anomaly. Fetuses were grouped based on gestational weeks, months and trimesters. Once general external measurements of the fetuses were carried out, the abdominal wall was dissected. The relationships between the duodenum and surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…We did not observe statistically significant differences when groups A and B were compared. The SIL and CL, the TBL, and the AL did not show any differences between the genders, in keeping with the findings in duodenal and vermiform appendix lengths reported by others [10,14]. In maceration, our study shows that only the CL is affected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not observe statistically significant differences when groups A and B were compared. The SIL and CL, the TBL, and the AL did not show any differences between the genders, in keeping with the findings in duodenal and vermiform appendix lengths reported by others [10,14]. In maceration, our study shows that only the CL is affected.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported that the total small and large intestinal lengths are decreased in the 3rd-pregnancy trimester IUGR fetuses [1]. The most recent and extensive work on the growth of the human fetal gastrointestinal tract originates from a single research group [10][11][12][13][14]. These authors did not focus on intestinal length measurements, although they do report that the lengths of the cecum and vermiform appendix increase with GA, and they give a length range of 5 to 45 mm for AL during the fetal period [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both points C and P were located near the midsagittal plane and gradually stabilized after CS20. A previous article described that the pyloric segment was also located near the midsagittal plane in the early fetal period (Desdicioglu et al, 2009). Hawass et al (1991) observed similar results, specifically that the axis between the gastroesophageal junction and pyloric canal was almost parallel to the long axis of the body at 7.5-8.5 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…Early in the fourth week, the duodenum begins to develop from the caudal end of the foregut, the cranial end of the midgut, and the splanchnic mesoderm which is the connection between these endodermal parts. [1] The villi and the crypts of Lieberkuhn begin to appear during the 8th week and 3rd month, respectively. [2] In addition, Brunner's glands appear in the proximal duodenum by 12-14 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, Brunner's glands appear in the proximal duodenum by 12-14 weeks. [1,2] The mature duodenum is lined by finger-like villi, which are shorter and blunter than those found in the Özet: ‹nsan fetüsünde duodenumun morfometrik analizi jejunum and ileum. The shortest villi are located in the proximal duodenum and become progressively longer distally.…”
Section: Introductionmentioning
confidence: 99%